2018
DOI: 10.3390/ijms19082157
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Biofilm Modulating Potential of Ferulic Acid-Grafted Chitosan against Human Pathogenic Bacteria

Abstract: The emergence of more virulent forms of human pathogenic bacteria with multi-drug resistance is a serious global issue and requires alternative control strategies. The current study focused on investigating the antibacterial and antibiofilm potential of ferulic acid-grafted chitosan (CFA) against Listeria monocytogenes (LM), Pseudomonas aeruginosa (PA), and Staphylococcus aureus (SA). The result showed that CFA at 64 µg/mL concentration exhibits bactericidal action against LM and SA (>4 log reduction) and bact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The results of the TCM antibacterial tests showed that F. mume (26.3 ± 0.50 mm), G. chinensis (23.7 ± 0.26 mm), R. codonopsis (20.0 ± 1.00 mm), P. granati (21.7 ± 0.36 mm), H. taraxaci (15.8 ± 0.85 mm) and R. coptidis (11.3 ± 1.6 mm) contained antibacterial components that exhibited antibacterial activity toward the ETEC strain K88, which is consistent with previously reported results [21,22]. F. mume exhibited a good antimicrobial effect on the ETEC K88 strain, potentially due to its high content of fumaric acid, which was previously shown to inhibit gram-positive and gram-negative bacteria [23][24][25]. In addition, gallic acid from G. chinensis inhibits bacterial growth by disrupting bacterial cell membranes, resulting in the leakage of cell contents [26].…”
Section: Resultssupporting
confidence: 88%
“…The results of the TCM antibacterial tests showed that F. mume (26.3 ± 0.50 mm), G. chinensis (23.7 ± 0.26 mm), R. codonopsis (20.0 ± 1.00 mm), P. granati (21.7 ± 0.36 mm), H. taraxaci (15.8 ± 0.85 mm) and R. coptidis (11.3 ± 1.6 mm) contained antibacterial components that exhibited antibacterial activity toward the ETEC strain K88, which is consistent with previously reported results [21,22]. F. mume exhibited a good antimicrobial effect on the ETEC K88 strain, potentially due to its high content of fumaric acid, which was previously shown to inhibit gram-positive and gram-negative bacteria [23][24][25]. In addition, gallic acid from G. chinensis inhibits bacterial growth by disrupting bacterial cell membranes, resulting in the leakage of cell contents [26].…”
Section: Resultssupporting
confidence: 88%
“…According to our knowledge, it is first study concerning the effects of these compounds against Aeromonas spp. The antibacterial activity of FA is due to its membrane-targeting action, which causes loss of membrane integrity [30]. Borges et al [31] showed that MBC value of FA for E. coli was 2500 μg/mL and 5000 μg/mL for S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…Resorcinol (entries 8 and 9) afforded two carboxylate products. Faber and coworkers have reported [45] the biocatalytic synthesis of salicylate derivatives starting from substituted phenols (as alkyl-, alkoxy-, halo-, and amino-substituted phenols) and HCO3 − by using 2,6-dihydroxybenzoate decarboxylase from Rhizobium sporomusa (2,6-DHBD_Rs), 2,3-dihydroxybenzoate decarboxylase from Aspergillus oryzae (2,, and salicylic acid decarboxylase from Trichosporon moniliiforme (SAD_Tm) (the general reaction is shown in Table 2, entries 1-3).…”
Section: Enzymatic Regioselective Ortho-carboxylation Of Phenols: Thementioning
confidence: 99%
“…Phenolic acids, encompassing both hydroxybenzoic and hydroxycinnamic acids (Figure 1), are important intermediates in the pharmaceutical and agrochemical industry, [1][2][3][4] as well as in the synthesis of advanced materials [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation